2019
DOI: 10.1016/j.alcohol.2018.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Wrist-worn alcohol biosensors: Strengths, limitations, and future directions

Abstract: Wearable alcohol biosensors have emerged as a valuable tool for noninvasive, objective and continuous monitoring of alcohol consumption. However, to date their research and clinical applications have been limited by several factors including large size, high cost, and social stigma. In contrast, recently developed wrist-worn alcohol biosensors are smaller, less expensive, and may be more acceptable for daily use. However, these devices are at the prototype phase and have just begun to be tested for research ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
118
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(123 citation statements)
references
References 34 publications
4
118
0
1
Order By: Relevance
“…Studies using WrisTAS in observational studies of young adults have reported device malfunction on approximately 18% of study days (Simons et al., ) and that only 38% of participants had a complete, interpretable data series over a 2‐week period (Luczak et al., ). Similar problems have been observed with newer sensor devices (Wang et al., ).…”
Section: Transdermal Alcohol Sensorssupporting
confidence: 72%
See 1 more Smart Citation
“…Studies using WrisTAS in observational studies of young adults have reported device malfunction on approximately 18% of study days (Simons et al., ) and that only 38% of participants had a complete, interpretable data series over a 2‐week period (Luczak et al., ). Similar problems have been observed with newer sensor devices (Wang et al., ).…”
Section: Transdermal Alcohol Sensorssupporting
confidence: 72%
“…Both devices contain electrochemical sensors to determine alcohol concentration in insensible perspiration in an enclosed area above the skin and have additional sensors measuring skin temperature and contact to confirm the device is being worn. Smaller and more efficient devices are being developed, but currently have limited commercial availability and lack supporting data (Wang et al., ).…”
Section: Transdermal Alcohol Sensorsmentioning
confidence: 99%
“…Some labs provide infectious disease testing services which can examine 4th generation HIV antibody testing using dried blood spot and chlamydia and gonorrhea testing using mail-in swabs, as well as mail-in samples for Hepatitis B and C testing [31][32][33]. Alcohol use can be remotely monitored using Bluetooth-enabled breathalyzers that estimate breath alcohol concentration or wrist-worn alcohol biosensors that continuously measure transdermal alcohol content [34][35][36].…”
Section: Monitoring and Assessmentmentioning
confidence: 99%
“…Skin permeability to ethanol is known to fluctuate over time [39], and therefore a flux-type sensor placed directly on the skin will measure the product of blood alcohol concentration and skin permeability, resulting in signals that vary with time [16]. The introduction of a diffusion-limiting membrane with known permeability converts a flux-type sensor into a continuous concentration sensor [40][41][42].…”
Section: Membranementioning
confidence: 99%
“…Continuous alcohol sensors have received growing interest from the research community [5][6][7][8][9][10][11][12][13][14], but commercial realizations thus far have involved trade-offs in performance [15,16]. The only two commercialized platforms (SCRAM and WrisTAS) use platinum fuel cells.…”
Section: Introductionmentioning
confidence: 99%